2021
DOI: 10.1002/ijc.33494
|View full text |Cite
|
Sign up to set email alerts
|

HOXD13 suppresses prostate cancer metastasis and BMP4‐induced epithelial‐mesenchymal transition by inhibiting SMAD1

Abstract: The HOX genes are a group of highly conserved Homeobox-containing genes that control the body plan organization during development. However, their contributions to tumorigenesis and tumor progression remain uncertain and controversial. Here we provided evidence of tumor-suppressive activity of HOXD13 in prostate cancer.HOXD13 depletion contributes to more aggressiveness of prostate cancer cells in vitro and in vivo. These effects were corroborated in a metastatic mice model, where we observed more bone metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In breast cancer, the methylation modification and low expression of the HOXD13 promoter are positively correlated with the poor prognosis of breast cancer patients 21,22 . In addition, HOXD13 inhibits prostate cancer metastasis and epithelial‐mesenchymal transition by inhibiting SMAD1 23 . This finding shows the plasticity of HOXD13 in the biological regulation of tumors and may be related to the properties of HOXD13 and transcription factors or cofactors.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In breast cancer, the methylation modification and low expression of the HOXD13 promoter are positively correlated with the poor prognosis of breast cancer patients 21,22 . In addition, HOXD13 inhibits prostate cancer metastasis and epithelial‐mesenchymal transition by inhibiting SMAD1 23 . This finding shows the plasticity of HOXD13 in the biological regulation of tumors and may be related to the properties of HOXD13 and transcription factors or cofactors.…”
Section: Discussionmentioning
confidence: 76%
“…21 , 22 In addition, HOXD13 inhibits prostate cancer metastasis and epithelial‐mesenchymal transition by inhibiting SMAD1. 23 This finding shows the plasticity of HOXD13 in the biological regulation of tumors and may be related to the properties of HOXD13 and transcription factors or cofactors. However, these findings need to be further verified by experiments.…”
Section: Discussionmentioning
confidence: 81%
“…More and more studies have demonstrated that the EMT process exerts a significant role on tumor progression and metastasis (7)(8)(9). The EMT program is associated with various pathways and crosstalk between these signaling by key molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EMT is not only associated with cancer cell proliferation, invasion and metastasis, but also with chemoresistance and cancer cell stemness. EMT is known as the initial step of the development of metastasis (5), existing in various tumors such as lung, pancreatic, liver and prostate carcinoma (6)(7)(8)(9). Resveratrol (RES) and its analogs reverse EMT to inhibit metastasis and mitigate chemoresistance via different pathways and mechanisms in human tumors (Tables 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mechanism studies have shown that hyperinflammatory type 2 diabetic islets secrete interleukin-1beta (IL-1β) and tumor necrosis factor-alpha (TNF-α), and stimulate MSC to secrete interleukin-1 receptor antagonist (IL-1Ra), and IL-1Ra inhibits islet inflammation, thereby reversing the dedifferentiation of β cells in type 2 diabetic islets and repairing islet function. Through this dialog response mechanism, MSCs can adjust the level of inflammation in the islets to a physiological range according to the need of the damaged islets and achieve a precise repair effect [ 19 , 20 ] (Table 2 ). In the treatment of diabetes-induced ulcers, the main ways of stem cell transplantation are intravascular injection and local injection.…”
Section: Applications Of Mscs In Diabetes Mellitusmentioning
confidence: 99%